Is the obesity paradox in outpatients with heart failure reduced ejection fraction real? - Salvino, Nathália Felix Araujo; Sousa, Lyz Tavares de; Abrahao, Fabio Maia; Spineti, Pedro Pimenta de Mello; Sales, Ana Luiza Ferreira; Neves de Albuquerque, Felipe; Bittencourt, Marcelo Imbroinise; de Moraes, Pedro Castello Branco; Esporcatte, Roberto; Mourilhe-Rocha, Ricardo (Frontiers in Cardiovascular Medicine, 2023)
Background: The obesity occurrence has achieved epidemic levels worldwide and several studies indicate a paradoxical similarity among obesity and the prognosis in heart failure (HF). The primary objective was to understand the association between body mass index (BMI) and heart failure with reduced ejection fraction (HFREF) of ischemic etiology in outpatients, using mortality as a parameter. The secondary objectives were to determine the differences in HF functional class, pharmacological therapy ang evaluate the prognostic value of MAGGIC Score in this population [1].Methods: We analyzed 1,556 medical records from the HF outpatient clinic of a quaternary hospital and 242 were selected according to the criteria. Most were male, average age 62.6 (56-70), BMI 18,5 to 24,9 = 35,1%, 25 to 29,9 = 37,2%, 30 to 34,9 = 17,8%, 35 to 39,9 = 7%; BMI <18,5 and > 40 groups were eliminated from the central analyzes because of scarce testing.Results: BMI 30 to 34,9 and BMI 18,5 to 24,9 had the best prognosis, BMI 25 to 29,9 had an average performance, and BMI 35 to 39,9 group provided the worst outcome (p=0.123). In the subcategory analysis, BMI 30 to 34,9 group had a better prognosis compared to the BMI 35 to 39,9 group (p=0.033). In the multivariate analysis The MAGGIC score was not able to foretell mortality in this population according to BMI.In not hospitalized patients with HFREF of ischemic etiology, obesity was not a protective factor.